2017
DOI: 10.1042/cs20171167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms contributing to cardiac remodelling

Abstract: Cardiac remodelling is classified as physiological (in response to growth, exercise and pregnancy) or pathological (in response to inflammation, ischaemia, ischaemia/reperfusion (I/R) injury, biomechanical stress, excess neurohormonal activation and excess afterload). Physiological remodelling of the heart is characterized by a fine-tuned and orchestrated process of beneficial adaptations. Pathological cardiac remodelling is the process of structural and functional changes in the left ventricle (LV) in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 258 publications
3
118
0
3
Order By: Relevance
“…P38 inhibitors (SB203580 or SB202190) suppressed hypertrophic stimuli induced myocyte growth and dominant negative P38 delivered by adenoviruses ( Zechner et al, 1997 ; Liang and Molkentin, 2003 ). Our previous studies have reported that many molecular and plant extracts ameliorate pressure overload-induced cardiac hypertrophy via MAPKs inhibition ( Wu et al, 2017b ). ATF3 exerts negative feedback on the ERK and JNK pathways to modulate cardiac remodeling ( Zhou et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…P38 inhibitors (SB203580 or SB202190) suppressed hypertrophic stimuli induced myocyte growth and dominant negative P38 delivered by adenoviruses ( Zechner et al, 1997 ; Liang and Molkentin, 2003 ). Our previous studies have reported that many molecular and plant extracts ameliorate pressure overload-induced cardiac hypertrophy via MAPKs inhibition ( Wu et al, 2017b ). ATF3 exerts negative feedback on the ERK and JNK pathways to modulate cardiac remodeling ( Zhou et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac remodelling involves myocyte hypertrophy, apoptosis and extracellular matrix accumulation. 2,29 We first observed the effects of Flt3 activation with the specific ligand FL on the function and morphology of maladaptive heart induced by continuous infusion of Ang II in mice. Echocardiographic analysis revealed that Ang II induced significant decreases in left ventricular ejection fraction (LVEF%), left ventricular fractional shortening (LVFS%) and left ventricular posterior wall thickness at end-diastole (LVPWd), but increases in left ventricular internal dimension at end-diastole (LVIDd).…”
Section: Flt3 Activation Improves Ang Iiinduced Cardiac Dysfunctionmentioning
confidence: 99%
“…Maladaptive cardiac remodelling is a chronic process in response to various pathologic stresses or diseases, which is intimately associated with the progression of heart failure (HF). [1][2][3] The hallmarks of adverse cardiac remodelling include progressive ventricular expansion, myocardial hypertrophy, fibrosis, cardiac performance deterioration and re-expression of foetal genes. 4,5 This process involves a dynamic change of many unknown genes, proteins and signalling molecules, thereby limiting the efficacious therapy of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacological interventions targeting these signaling pathways may provide promising approaches for preventing cardiac hypertrophy. Unfortunately, despite the clinical use of angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and β-blockers, the death rate due to heart failure is increasing every year [2]. Thus, a better understanding of the intracellular signaling pathways that mediate cardiac hypertrophy and identification of novel drugs that disrupt the intracellular signaling pathways are greatly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, during hypertrophy, myocytes grow in size and contribute to protein synthesis [2]. Although this response may be initially beneficial, sustained cardiac hypertrophy ultimately leads to ventricular dilation and congestive heart failure [3].…”
Section: Introductionmentioning
confidence: 99%